2017
DOI: 10.1016/j.bbr.2016.09.047
|View full text |Cite
|
Sign up to set email alerts
|

NMDAR dependent intracellular responses associated with cocaine conditioned place preference behavior

Abstract: The aim of this study was to investigate the intracellular responses associated with the acquisition and expression of cocaine-context associations. ERK (extracellular regulated kinase), CREB (cAMP responsive element binding protein), FosB and ΔFosB proteins were of particular interest due to their involvement in cocaine reward and in synaptic plasticity underlying learning and memory. We used the conditioned place preference (CPP) paradigm, which employs a Pavlovian conditioning procedure to establish an asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Significantly the present study found deficits in object-in-place memory following both a 6 and 24 h retention delay, but not at 5 min or 3 h. A retention delay of 6 h is much shorter than had been investigated in previous studies (Bourtchuladze et al 1994;Guzowski and McGaugh 1997;Peters et al 2009), and the deficit at this timepoint indicates that CREB phosphorylation is an important step in a cellular pathway for the stabilization of memory information between 3 and 6 h following learning. From our previous studies initiation of this cellular pathway appears to depend on the activation of specific receptor subtypes in the mPFC such as the NMDA and D1/D5 receptor and blockade of these receptors impairs both object-in-place Warburton 2008, 2011b;Savalli et al 2015), and temporal order memory (Hotte et al 2006) and interestingly activation of the NMDA and D1/D5 receptors has been shown to be crucial for CREB phosphorylation (Pittenger et al 2002;Hotte et al 2006;Olianas et al 2012;Kirschmann et al 2014;Nygard et al 2017). CREB expression is regulated at transcriptional level by epigenetic mechanisms such as DNA methylation (Chahrour et al 2008) and we have shown that disruption of DNA methylation impairs longterm object-in-place memory (Chahrour et al 2008;Scott et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Significantly the present study found deficits in object-in-place memory following both a 6 and 24 h retention delay, but not at 5 min or 3 h. A retention delay of 6 h is much shorter than had been investigated in previous studies (Bourtchuladze et al 1994;Guzowski and McGaugh 1997;Peters et al 2009), and the deficit at this timepoint indicates that CREB phosphorylation is an important step in a cellular pathway for the stabilization of memory information between 3 and 6 h following learning. From our previous studies initiation of this cellular pathway appears to depend on the activation of specific receptor subtypes in the mPFC such as the NMDA and D1/D5 receptor and blockade of these receptors impairs both object-in-place Warburton 2008, 2011b;Savalli et al 2015), and temporal order memory (Hotte et al 2006) and interestingly activation of the NMDA and D1/D5 receptors has been shown to be crucial for CREB phosphorylation (Pittenger et al 2002;Hotte et al 2006;Olianas et al 2012;Kirschmann et al 2014;Nygard et al 2017). CREB expression is regulated at transcriptional level by epigenetic mechanisms such as DNA methylation (Chahrour et al 2008) and we have shown that disruption of DNA methylation impairs longterm object-in-place memory (Chahrour et al 2008;Scott et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Blocking NMDAR with MK-801 before datumetine treatment indicates that the effect of datumetine was reversed in the PFC as the level of CamKIIα was higher in MK-801+ datumetine mice than datumetine mice. This shows that datumetine specifically binds to NMDAR in the PFC as MK-801 is a known NMDAR antagonist ( Amalric et al, 1994 ; Nygard et al, 2017 ; Sean et al, 2013; Singh et al, 1990 ; Vishnoi et al, 2015 ; Xue et al, 2011 ) MK801, prevented increases in striatal and nigral levels of NT following both single and multiple administrations of methamphetamine. Significant attenuation of the methamphetamine-induced changes in the striatal NT system were observed with MK801 doses as low as 0.01 mg/kg per dose.…”
Section: Discussionmentioning
confidence: 86%
“…Blocking NMDAR with MK-801 before datumetine treatment indicates that the effect of datumetine was reversed in the PFC as the level of CamKIIα was higher in MK-801+Datumetine mice than Datumetine mice. This shows that datumetine binds specifically to NMDAR in the PFC as MK-801 is a known NMDAR antagonist (Amalric et al, 1994;Nygard et al, 2017;Sean et al, 2013;Singh et al, 1990;Vishnoi et al, 2015;Xue et al, 2011).…”
Section: Discussionmentioning
confidence: 87%
“…Yet, reexposure only to the cocaine-paired compartment yielded to activated ERK in the NAc when the reexposure occurred one day after the CPP test (Nygard et al, 2015) but not two days after the CPP test (Tropea et al, 2008). When evaluated directly after the CPP test without reexposure to cocaine or to the cocaine-associated context, ERK was activated in the NAc of animals conditioned with the drug at the dose of 20 mg/kg (Valjent et al, 2006;Nygard et al, 2013Nygard et al, , 2017. On the other hand, phospho-ERK was reported to increase only in the core but not the shell subdivision of the NAc after the CPP test to cocaine at a dose of 10 mg/kg (Miller and Marshall, 2005).…”
Section: Discussionmentioning
confidence: 98%